An injectable self-healing hydrogel with adhesive and antibacterial properties effectively promotes wound healing. (1st December 2018) - Chen, Honglei; Cheng, Junwen; Ran, Luoxiao; Yu, Kun; Lu, Bitao; Lan, Guangqian; Dai, Fangying; Lu, Fei
Highlights: KGM is oxidized to aldehyde konjac glucomannan that was used as a polymer cross-linker. The hydrogel has good biocompatibility and adhesion. The hydrogel has good self-healing ability and can effectively inhibit bacterial proliferation. The hydrogel can accelerate wound contraction and promote wound healing. Abstract: Hydrogels with self-healing capacity can undergo self-repair, establishing safer and longer-lasting products. Hydrogel wound dressings showing self-healing capacity can prolong the lifespan of the material and provide better wound protection. Therefore, in this study, Schiff base reactions (reversible imine linkages) were utilized to design injectable self-healing hydrogels with chitosan and konjac glucomannan. Oxidized konjac glucomannan was used to react with chitosan to form hydrogel. In addition to injectable, self-healing properties, the hydrogels also had adhesive and antibacterial properties, were biocompatible, and promoted wound healing. The inhibition rates of hydrogels against Staphylococcus aureus and Escherichia coli were 96% and 98%, respectively. In addition, microscopy and rheological analyses showed that the hydrogels healed within 4 h without additional exogenous stimulation. Finally, the developed hydrogels were injectable and significantly shortened wound recovery time in a full-thickness skin defect model. Thus, our findings established a novel hydrogel material that may have applications in wound healing.